2022
DOI: 10.3389/fcvm.2022.996744
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of different types of cardioplegia in cardiac surgery: A network meta-analysis

Abstract: ObjectiveTo compare the outcomes of four types of cardioplegia during cardiac surgery: del Nido (DN), blood cardioplegia (BC), histidine-tryptophan-ketoglutarate (HTK) and St. Thomas.MethodsRandomized controlled trials (RCTs) and observational cohort studies from 2005 to 2021 were identified in PubMed, Embase, and Cochrane databases. Data were extracted for the primary endpoint of perioperative mortality as well as the following secondary endpoints: atrial fibrillation, renal failure, stroke, use of an intra-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Our finding that mixed blood-crystalloid cardioplegia led to better outcomes than entirely crystalloid cardioplegia is consistent with studies that have associated HTK cardioplegia with lower cardiac index and ventricular function soon after surgery ( 25 ) and higher incidence in spontaneous ventricular fibrillation ( 26 ) than cold blood cardioplegia. Our network meta-analysis comparing several types of cardioplegia solutions containing only crystalloid or a combination of crystalloid and blood linked HTK cardioplegia solution to the highest risk of mortality ( 27 ). This evidence base argues for including a substantial component of natural blood in cardioplegia solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that mixed blood-crystalloid cardioplegia led to better outcomes than entirely crystalloid cardioplegia is consistent with studies that have associated HTK cardioplegia with lower cardiac index and ventricular function soon after surgery ( 25 ) and higher incidence in spontaneous ventricular fibrillation ( 26 ) than cold blood cardioplegia. Our network meta-analysis comparing several types of cardioplegia solutions containing only crystalloid or a combination of crystalloid and blood linked HTK cardioplegia solution to the highest risk of mortality ( 27 ). This evidence base argues for including a substantial component of natural blood in cardioplegia solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Blood cardioplegia is the standard of care in pediatric cardiac surgery [ 14 ]; however, there is a tendency to shift to single-dose cardioplegia to minimize the interruption of surgical operation [ 15 ]. Therefore, intracellular solutions such as Custodiol and Del-Nido cardioplegia are currently increasingly used in pediatric cardiac surgery [ 16 ]. Bibevski and associates found no difference between Custodiol and blood cardioplegia in left and right ventricular function; however, the inotropic support was lower with Custodiol cardioplegia [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Giordano and colleagues [ 19 ] and Bojan and coworkers [ 20 ] found no difference in the clinical outcomes between Custodiol and blood cardioplegia. In a meta-analysis of 12 studies containing 1,634 pediatric patients, four types of cardioplegia were compared [ 16 ]. The study reported no difference in mortality between Custodiol, Del-Nido, and St. Thomas and blood cardioplegia.…”
Section: Discussionmentioning
confidence: 99%
“…A network meta-analysis of 18 randomized controlled trials and 49 observational cohort studies (n = 18,191) which compared different types of commonly used well-defined cardioplegia solutions (crystalloid materials and mixtures of crystalloids and blood products) demonstrated that use of a 4:1 mixture of crystalloid solution and blood products (del Nido cardioplegia) may be associated with lower perioperative mortality. 23 Mitigation of leukocyte-induced myocardial inflammation and calcium overload due to low levels of leukocytes and calcium ions contained in the solution could theoretically explain the outcome benefit shown in the meta-analysis. 23 This notion, however, should be further examined in large prospective studies.…”
Section: Cardiopulmonary Bypass and Myocardial Protectionmentioning
confidence: 98%